If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2X + 2) + -4(3X + 2) = 5X + 20 Reorder the terms: 3(2 + 2X) + -4(3X + 2) = 5X + 20 (2 * 3 + 2X * 3) + -4(3X + 2) = 5X + 20 (6 + 6X) + -4(3X + 2) = 5X + 20 Reorder the terms: 6 + 6X + -4(2 + 3X) = 5X + 20 6 + 6X + (2 * -4 + 3X * -4) = 5X + 20 6 + 6X + (-8 + -12X) = 5X + 20 Reorder the terms: 6 + -8 + 6X + -12X = 5X + 20 Combine like terms: 6 + -8 = -2 -2 + 6X + -12X = 5X + 20 Combine like terms: 6X + -12X = -6X -2 + -6X = 5X + 20 Reorder the terms: -2 + -6X = 20 + 5X Solving -2 + -6X = 20 + 5X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-5X' to each side of the equation. -2 + -6X + -5X = 20 + 5X + -5X Combine like terms: -6X + -5X = -11X -2 + -11X = 20 + 5X + -5X Combine like terms: 5X + -5X = 0 -2 + -11X = 20 + 0 -2 + -11X = 20 Add '2' to each side of the equation. -2 + 2 + -11X = 20 + 2 Combine like terms: -2 + 2 = 0 0 + -11X = 20 + 2 -11X = 20 + 2 Combine like terms: 20 + 2 = 22 -11X = 22 Divide each side by '-11'. X = -2 Simplifying X = -2
| (6x-3)=(4x+7) | | 2x=(360+2) | | (6)*(3x+2)=(6)*(5x-10) | | R(6x-3)=(4x+7) | | 5n-2(n-2)=-11+3n+5 | | 4y+2=8(y+7) | | 5(-9+x)=-25 | | 6(2+x)=72 | | -2x-30=28-4x | | (3)*(2x+9)=27 | | -8u-30=-6(u+7) | | -3rs(2r^2s+12t-7)= | | -2x-66=62-10x | | 4(x-7)=7x-13 | | K-15=-40 | | -55-2x=-5x+17 | | -5(1+4x)=195 | | 2n+8=3(n-9) | | 3y+18=-6(y-9) | | -31-7x=17-11x | | -3x+5(-9+4x)=-x-4 | | (4)*(3x+12)=64 | | -76+7x=104-2x | | 12x-25=7x+35 | | -4x-14=-7x+12 | | 5x-2(-2x+19)=-83 | | 3(1x+5)=42 | | 8x-68=77+4x | | 3x-6(1+x)=-9x+9 | | 3b-50=4b-74 | | -124+12x=5x+86 | | 9x^2+4x+87=180 |